Effect of sawdust mulch on soil properties and performance of tomatoes (Lycopersicum esculentum) in an alfisol in Southwestern Nigeria - Femi Olusola Abiodun; Isola John Oluwasina (Journal of Agricultural Sciences (Belgrade), 2023)
Mulching is an effective method of manipulating crop growing environment to increase yield. A field experiment was carried out at the Teaching and Research Farm of the Federal College of Forestry Jericho (Ibadan). The study aimed to examine the effect of sawdust mulching on selected soil properties, growth and yield of two tomato varieties. The study was a 4 x 2 factorial experiment laid out in a randomized completely block design (RCBD) with four replications. Factor one consisted of four treatments, namely: T0 (control), T1 (sawdust mulch [SDM] at 10 t ha-1 ), T2 (SDM at 20 t ha -1 ) and T3 (SDM at 30 t ha1 ). The second factor was the two tomato varieties (UC82B and Ibadan local). Plant height, stem girth, number of leaves and branches were collected at a 2-week interval while the number of fruits, fruit weight (kg/ha) and yield parameters were measured at maturity. The Genstat statistical software package was used for data analysis and an LSD test was performed at the 5% level of significance. The sawdust mulch used had a low nitrogen content (0.60%) and a moderate organic carbon content (38.6%). The use of sawdust mulch had a major impact on tomato yield, while there was not any significant variation among the examined tomato varieties. UC82B (117.92 kg ha-1 ) at 30 t ha-1 SDM plot had the highest yield, followed by Ibadan local (103.93 kg ha-1 ) at 30 t ha-1 SDM plot, while Ibadan local (61.94 kg ha-1 ) at the control plot had the lowest yield. In this study, the tomato performed best with sawdust mulch at 30 t ha-1 and is therefore recommended to farmers in the study area to maximize tomato production.